2006
DOI: 10.1111/j.1467-9248.2006.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Territory and PowerRevisited: Theorising Territorial Politics in the United Kingdom after Devolution

Abstract: The article seeks to contribute to theoretical analysis of political decentralisation in the UK occasioned by devolution to Scotland, Wales and Northern Ireland in 1998–9. It examines the contribution that can be made by Jim Bulpitt's 1983 book, Territory and Power in the United Kingdom. First, it argues that Bulpitt's critique of conventional wisdoms in the early 1980s remains highly relevant to reflecting on shortcomings in the literature today. Key among these is the lack of a common conceptual language for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…With most of the academics working in the field, the debt to Bulpitt is implicit rather than direct. The exception is Bradbury (2006) who uses 'y the underlying problem is the samehow to develop a form of statecraft that allows the central authority to sustain itself over time and to reward the interests of its governing elites'.…”
Section: The Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…With most of the academics working in the field, the debt to Bulpitt is implicit rather than direct. The exception is Bradbury (2006) who uses 'y the underlying problem is the samehow to develop a form of statecraft that allows the central authority to sustain itself over time and to reward the interests of its governing elites'.…”
Section: The Conceptsmentioning
confidence: 99%
“…It concerns economic interests, pressure groups and the political parties, which are differently constituted in the various territories of the nation state. This term, and the analysis behind it, has stimulated a stream of work in the UK political science (e.g., Rhodes, 1988), which is now labelled as territorial politics (Bradbury, 2006). Territorial politics scholars fully acknowledge the importance of the state as a concept to understand the exercise of power and authority and places historical context at the centre of political analysis.…”
Section: The Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…A generation ago, at the time of the devolution debates in the 1970s, a similar existential question was asked by scholars in the Work Group on United Kingdom Politics. Jonathan Bradbury (2006), in order to highlight some of the shortcomings of the contemporary literature, has profitably and subtly re-examined, in the light of devolution, the insights of Jim Bulpitt's (1983) book Territory and Power in the United Kingdom. This article looks at another of that group's seminal thinkers, Richard Rose, and specifically re-examines the utility of 'fifth nation' to conceptualise the contemporary United Kingdom.…”
Section: Introductionmentioning
confidence: 98%
“…British territorial management was therefore a history of continuity rather than change based around a 'dual polity' whereby the national government preferred to concentrate on 'high politics'. Analyses of Scotland, Wales and Northern Ireland through a Bulpittian framework have concluded that the central autonomy model remains dominant there despite the strength of devolved powers (Bradbury, 2006;Convery, 2014). Our Bulpittian analysis continues in this historical and qualitative vein to look at the political imperatives shaping the most recent chapter in English territorial governance.…”
Section: Bulpitt's Frameworkmentioning
confidence: 99%